ANALISIS MOTIVASI KERJA DAN KINERJA KARYAWAN DI KLINIK PUSAT BEKAM DAN RUQYAH PEDURENAN - MUHAMMAD NUR ISHAK (DIRHAM Jurnal Ekonomi Islam, 2021)
Work motivation and employee performance have an important role in the running of the company, in this case, the Cupping Center Clinic and Ruqyah, as well as to meet the service standards that have been determined and to be able to survive in the competition amid the rampant business of similar types lately. In this study, the authors wanted to analyze the work motivation and performance of employees at the Center of Cupping and Ruqyah Pedurenan clinics using qualitative methods by interviewing several employees and heads of clinic branches of the Center for Cupping and Ruqiyah Pedurenan. And with this research, the authors conclude that employees of the Central Cupping Center Clinic and Ruqyah Pedurenan employees are less satisfied with the salary received, and the work motivation and performance of employees decrease, even though employees still have the motivation to survive because of several factors including life necessities, but more It is important to want to create a better work environment because with work motivation and good performance hope to be able to improve work careers and also change in income.